Immunotoxicity and genotoxicity testing of PLGA-PEO nanoparticles in human blood cell model. Issue 1 (May 2015) - Tulinska, Jana; Kazimirova, Alena; Kuricova, Miroslava; Barancokova, Magdalena; Liskova, Aurelia; Neubauerova, Eva; Drlickova, Martina; Ciampor, Fedor; Vavra, Ivo; Bilanicova, Dagmar; Pojana, Giulio; Staruchova, Marta; et al.
Abstract A human blood cell model for immunotoxicity and genotoxicity testing was used to measure the response to polylactic-co-glycolic acid (PLGA-PEO) nanoparticle (NP) (0.12, 3, 15 and 75 μg/cm2 exposure in fresh peripheral whole blood cultures/isolated peripheral blood mononuclear cell cultures from human volunteers (n = 9–13). PLGA-PEO NPs were not toxic up to dose 3 μg/cm2; dose of 75 μg/cm2 displays significant decrease in [3H]-thymidine incorporation into DNA of proliferating cells after 4 h (70% of control) and 48 h (84%) exposure to NPs. In non-cytotoxic concentrations, in vitro assessment of the immunotoxic effects displayed moderate but significant suppression of proliferative activity of T-lymphocytes and T-dependent B-cell response in cultures stimulated with PWM > CON A, and no changes in PHA cultures. Decrease in proliferative function was the most significant in T-cells stimulated with CD3 antigen (up to 84%). Cytotoxicity of natural killer cells was suppressed moderately (92%) but significantly in middle-dosed cultures (4 h exposure). On the other hand, in low PLGA-PEO NPs dosed cultures, significant stimulation of phagocytic activity of granulocytes (119%) > monocytes (117%) and respiratory burst of phagocytes (122%) was recorded. Genotoxicity assessment revealed no increase in the number of micronucleated binucleated cells and no induction of SBs or oxidised DNA bases in PLGA-PEO-treated cells. To conclude on immuno- and genotoxicity of PLGA-PEO NPs, more experiments with various particle size, charge and composition need to be done.